Production of Recombinant Trichoderma reesei Cellobiohydrolase II in a New Expression System Based on Wickerhamomyces anomalus. (30th August 2017) - Díaz-Rincón, Dennis J.; Duque, Ivonne; Osorio, Erika; Rodríguez-López, Alexander; Espejo-Mojica, Angela; Parra-Giraldo, Claudia M.; Poutou-Piñales, Raúl A.; Alméciga-Díaz, Carlos J.; Quevedo-Hidalgo, Balkys
Abstract : Cellulase is a family of at least three groups of enzymes that participate in the sequential hydrolysis of cellulose. Recombinant expression of cellulases might allow reducing their production times and increasing the low proteins concentrations obtained with filamentous fungi. In this study, we describe the production of Trichoderma reesei cellobiohydrolase II (CBHII) in a native strain of Wickerhamomyces anomalus . Recombinant CBHII was expressed in W. anomalus 54-A reaching enzyme activity values of up to 14.5 U L −1 . The enzyme extract showed optimum pH and temperature of 5.0–6.0 and 40°C, respectively. Enzyme kinetic parameters (K M of 2.73 mM and V max of 23.1  µ M min −1 ) were between the ranges of values reported for other CBHII enzymes. Finally, the results showed that an enzymatic extract of W. anomalus 54-A carrying the recombinant T. reesei CBHII allows production of reducing sugars similar to that of a crude extract from cellulolytic fungi. These results show the first report on the use of W. anomalus as a host to produce recombinant proteins. In addition, recombinant T. reesei CBHII enzyme could potentially be used in the degradation of lignocellulosic residues to produce bioethanol, based on its pH and temperature activity profile.